Material setting and reform experience in English institutions for fallen women, 1838-1910: inside the homes of mercy - Woodall, Susan (Genders and sexualities in history, 2023)
Tracing the history of four English case studies, this book explores how, from outward appearance to interior furnishings, the material worlds of reform institutions for 'fallen' women reflected their moral purpose and shaped the lived experience of their inmates. Variously known as asylums, refuges, magdalens, penitentiaries, Houses or Homes of Mercy, the goal of such institutions was the moral 'rehabilitation' of unmarried but sexually experienced 'fallen' women. Largely from the working-classes, such women - some of whom had been sex workers - were represented in contradictory terms. Morally tainted and a potential threat to respectable family life, they were also worthy of pity and in need of 'saving' from further sin. Fuelled by rising prostitution rates, from the early decades of the nineteenth century the number of moral reform institutions for 'fallen' women expanded across Britain and Ireland. Through a programme of laundry, sewing work and regular religious instruction, the period of institutionalisation and moral re-education of around two years was designed to bring about a change in behaviour, readying inmates for economic self-sufficiency and re-entry into society in respectable domestic service. To achieve their goal, institutional authorities deployed an array of ritual, material, religious and disciplinary tools, with mixed results